2004
DOI: 10.3317/jraas.2004.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of candesartan and lisinopril alone and in combination on blood pressure and microalbuminuria

Abstract: BackgroundAngiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blocking drugs (ARB) block the effect of angiotensin II by different mechanisms. It has been suggested that combined therapy may be more effective at reducing blood pressure (BP) than higher doses of either drug. MethodsTwenty-three elderly patients with systolic hypertension completed a double-blind crossover study comparing placebo, candesartan (C) 16 mg, C32 mg, lisinopril (L) 20 mg, L40 mg and C16 mg + L20 mg. Treatment perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Our results indicate the importance of the self-limitation of a single-drug RAS blockade, and this has major consequences for selecting both the timing of drug administration (28) and the daily dosage (7). Besides this physiologic interpretation, intraindividual variations in drug pharmacokinetics may contribute in hypertensive (29) and renal (30) patients to the recruitment of nonresponders by a second blocker acting at another site, within the limits imposed by the variable participation of the RAS in individual BP control (31).…”
Section: Combined Blockade Of the Ras By Aliskiren And Valsartanmentioning
confidence: 85%
“…Our results indicate the importance of the self-limitation of a single-drug RAS blockade, and this has major consequences for selecting both the timing of drug administration (28) and the daily dosage (7). Besides this physiologic interpretation, intraindividual variations in drug pharmacokinetics may contribute in hypertensive (29) and renal (30) patients to the recruitment of nonresponders by a second blocker acting at another site, within the limits imposed by the variable participation of the RAS in individual BP control (31).…”
Section: Combined Blockade Of the Ras By Aliskiren And Valsartanmentioning
confidence: 85%
“…12 Second, Morgan et al found that a combination of candesartan 16 mg plus lisinopril 20 mg (both once daily) had an additive effect on clinic BP only when compared with monotherapy with lisinopril 20 mg, but not when compared with lisinopril 40 mg or candesartan 16 mg or 32 mg. 25 Finally, Forclaz et al have shown, in normotensive individuals, that a supramaximal dose of losartan achieves equivalent RAS inhibition to a combination of losartan plus lisinopril, particularly if the former is administered twice daily. 26 In addition to concerns relating to dosage and dosage intervals, it should be emphasized that these studies were generally of short duration (4 to 8 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Thus disease was ameliorated, but not prevented. When large clinical trials using Ang II blockade in patients with overt diabetic nephropathy were reported, they too found amelioration but not prevention of nephropathy [6][7][8]. These results in rats and in humans suggested that additional pathways lead to TGF-and PAI-1 production.…”
Section: Introductionmentioning
confidence: 94%